2020
DOI: 10.1049/iet-sen.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Requirement patterns: a tertiary study and a research agenda

Abstract: The low performance of software projects generally arises from erroneous, omitted, misinterpreted, or conflicting requirements. To produce better quality specifications, the practise of requirements reuse through requirement patterns has been widely debated in the secondary literature. However, a tertiary study that provides an overview of secondary studies on the state of the art and the practise of requirement patterns does not exist. This study describes a study of secondary literature on requirement patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…This section's goal is three-fold: first, it introduces research method types that helped ground the doctoral project; second, it describes two systematic studies performed from planning to results analysis; and it demonstrates how these studies' results contributed to the definition of the PhD research proposal (Kudo, 2021). Figure 1 illustrates how the best available evidence provided by the systematic studies -tertiary review (Kudo et al, 2020a) and systematic mappings (Kudo et al, 2019a,b) -guided decisions during the PhD project reported in this paper. Each step in Figure 1 is described next.…”
Section: From Systematic Studies To a Phd Research Projectmentioning
confidence: 99%
“…This section's goal is three-fold: first, it introduces research method types that helped ground the doctoral project; second, it describes two systematic studies performed from planning to results analysis; and it demonstrates how these studies' results contributed to the definition of the PhD research proposal (Kudo, 2021). Figure 1 illustrates how the best available evidence provided by the systematic studies -tertiary review (Kudo et al, 2020a) and systematic mappings (Kudo et al, 2019a,b) -guided decisions during the PhD project reported in this paper. Each step in Figure 1 is described next.…”
Section: From Systematic Studies To a Phd Research Projectmentioning
confidence: 99%
“…We have strictly followed the guidelines proposed by Kitchenham and Charters, 23 Kitchenham et al, 22 Petersen et al, 24 and Petersen et al 25 to achieve an impartial review. These guidelines have been widely adopted in SLR, surveys, and SMS 41‐44 …”
Section: Planning and Conducting The Mappingmentioning
confidence: 99%
“…The Table III Fig. 4: A detail view of the identification and selection processes of primary studies, adapted from [42]. shows the result of this process for each digital library.…”
Section: B Conductingmentioning
confidence: 99%
“…Importantly, criterion 4 was responsible for the largest number of excluded articles, followed by criterion 5, and criteria 2 and 7 were the least responsible. This is because, in most systematic studies, small rates of return often occur for studies relevant to the research topic studied [36], [42]. Compared to criteria 2 and 7, it is agreend that most publications are in the English language and unique versions.…”
Section: B Conductingmentioning
confidence: 99%